Enhanced UMTS Deployment and Mobility Scenarios - Ferreira, Jaime (2003)
An overview of Enhanced UMTS (E-UMTS) deployment scenarios and supported services is presented, based on the views of nowadays-relevant players. The influence of mobility in E-UMTS is discussed and a set of mobility models is given. Then, a set of scenarios is described, that put together the most important components of E-UMTS deployment situations. These include expected population density, mobility characteristics, and expected usage of service mix, for each environment. A number of nearly thirty applications, divided into in five groups (Sound, High Interactive Multimedia, Narrowband, Wideband, Broadband), is considered.